2018
DOI: 10.4081/jbr.2018.7516
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus infection among hemodialysis patients

Abstract: Hepatitis B virus is a major public health impasse all over the world. Recently a new form of hepatitis B infection named Occult hepatitis B Infection (OBI) has appeared globally. The OBI is defined as the presence of HBV DNA in the liver and/or blood in the absence of detectable serum HBsAg with/without anti-HBc or anti-HBs. The prevalence of OBI has been reported in hemodialysis (HD) patients in different regions of the world. Thus, this study investigated the prevalence of OBI among HD patients. The cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…This screening policy in combination with dialysis-specific preventive measures, including isolation decisions, training the medical staff and active vaccination, can minimize the risk of HBV transmission in dialysis centers. 4 The prevalence of 10.4% for occult HBV infection reported in this study is higher than those observed among hemodialysis patients in the other parts of Iran, 0.0% in Guilan (northern Iran), 19 0.0% in Isfahan (central Iran), 18 0.8% in Yazd (central Iran), 17 0.5% in Tehran (north-central Iran), 20 4.7% in Ahvaz (southwestern Iran), 21 and 6% in Zanjan (western Iran). 22 The prevalence of occult HBV infection detected in this study is also higher than those reported among hemodialysis patients of some other regions and countries, 0.0% in Al-Nasiriyah, Iraq 23 ; 0.3% in eastern Japan 24 ; 0.9% in central Greece 25 ; 1.3% in South Korea 26 ; 2.2% in London, United Kingdom 27 ; and 2.3% in northeastern Brazil 28 but lower than those reported among hemodialysis patients in Egypt (32%) 29 and Sudan (15.9%).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…This screening policy in combination with dialysis-specific preventive measures, including isolation decisions, training the medical staff and active vaccination, can minimize the risk of HBV transmission in dialysis centers. 4 The prevalence of 10.4% for occult HBV infection reported in this study is higher than those observed among hemodialysis patients in the other parts of Iran, 0.0% in Guilan (northern Iran), 19 0.0% in Isfahan (central Iran), 18 0.8% in Yazd (central Iran), 17 0.5% in Tehran (north-central Iran), 20 4.7% in Ahvaz (southwestern Iran), 21 and 6% in Zanjan (western Iran). 22 The prevalence of occult HBV infection detected in this study is also higher than those reported among hemodialysis patients of some other regions and countries, 0.0% in Al-Nasiriyah, Iraq 23 ; 0.3% in eastern Japan 24 ; 0.9% in central Greece 25 ; 1.3% in South Korea 26 ; 2.2% in London, United Kingdom 27 ; and 2.3% in northeastern Brazil 28 but lower than those reported among hemodialysis patients in Egypt (32%) 29 and Sudan (15.9%).…”
Section: Discussioncontrasting
confidence: 49%
“…2 In addition, those studies using real-time PCR assay 17,18,20 to detect HBV DNA have reported a lower prevalence rate than the studies using nested PCR assay. 21,22,32 However, the probability of contamination with PCR product during procedures that can result in false-positive results considers as the main limitation of the nested-PCR method. 31 In the present study, strict quality controls and positive and negative controls were applied to avoid contamination and to ensure the accuracy of the results.…”
Section: Discussionmentioning
confidence: 99%